THE INFLUENCE OF PEER RELATIONSHIPS ON SMOKING BEHAVIOR & DRUG ABUSE IN ADOLESCENTS - Susanti, Nofi; Adawiyah, Azzahra Al; Pratiwi, Atikah; Siregar, Nadia Safira; Inayah, Fiqih (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Basically, teenage behavior is a time when they are looking for their identity and want the freedom to do things they like and want. Smoking behavior and drug abuse are still problems in the current era of globalization. The influence of peer relationships is the main factor in influencing a teenager's attitudes and behavior towards using cigarettes and drugs. The aim of this research is to determine the influence of peer relationships on smoking behavior and drug abuse in adolescents. This research method is a literature review, which involves collecting data by understanding and studying theories from various literature that is relevant to the research. The results of the research stated that based on the 3 factors identified, namely, invitations or persuasion from friends had a higher percentage compared to the behavior of wanting to try and stress due to the burden of studying/learning work/work. The conclusion of this research is that the influence of peer relationships is the main factor in influencing teenagers' attitudes and behavior regarding cigarette and drug use.